An Evidence-Based Approach to the Differentiation of Compressive Neuropathy from Polysensory Neuropathy in the Upper Extremity. Issue 10 (October 2017) - Raducha, Jeremy E.; Gil, Joseph A.; DeFroda, Steven F.; Wawrzynski, Joseph; Weiss, Arnold-Peter C.
Abstract : Compressive neuropathies present with focal symptoms. Polysensory neuropathies present with multifocal or symmetric symptoms. Clinical examination alone can differentiate between compressive and polysensory neuropathy. Electrodiagnostic studies can distinguish between types of polysensory neuropathies.